Yu. I KALASHNYK: STYLISTIC AND SYNTACTIC ORGANIZATION OF PHILOSOPHICAL MAXIMS IN V. YERMOLENKO’S NOVEL «OCEAN CATCHER. THE HISTORY OF ODYSSEUS» - KALASHNYK, Yu. I. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Introduction. The narrative of a work of art is a complex, polyphonic phenomenon, in which the leading role belongs to the narrator, who often conveys the author’s views on the reflected. V. Yermolenko’s novel «Ocean Catcher. The History of Odysseus» is marked by a wealth of verbal images associated with the embodiment of philosophical motives, aphoristic presentation, but it has not yet been the subject of special linguistic research, which determines the relevance of our study. Purpose. Identify the features of the use of stylistic and syntactic tools and techniques in the language of V. Yermolenko’s novel «Ocean Catcher. The History of Odysseus» in order to express philosophical maxims. Results. The analyzed philosophical statements in the novel mainly have the structure of compound sentences, mostly complex with different subordinate parts. If a subordinate part refers to definitions in which the noun compound predicate in the main part is a reference word, then the subordinate part is an adnominal-defining. Sometimes the writer reinterprets stereotypical expressions, presenting them with the construction of a complex sentence with a subordinate explanatory part, which accordingly has a supporting verb to say. Moral and ethical concepts of cruelty and confidence are understood in a complex unconnected sentence of a minimal structure, which creates a certain rhythm. The expression of the sentence determines the use in the anaphoric repetition of the pronoun everyone, which sets the generalizing semantics of the expression. Some sentences are expressed by rhetorical questions. Derivative repetition in adjacent sentences and anaphoric repetition of the interrogative participle were used to express the opinion. Sentences in the language of the novel are characterized by constructions with a subject and a predicate, expressed in one part of speech. V. Yermolenko creates individual-author conceptual metaphorical images. Structures of this type contribute not only to the accuracy of an expression, but also acertain categoricalness. Syntactic parallelism with repetition, accompanied by a change in the form of predicates and the subject and object to them, contributes to the perception of the above. In this way, the thought seems to go in a circle and is compressed like a spring, in order to move into the opposition, which is amplified by the previous statement. The expression is created by rhetorical objections. In the main part of a complex sentence, the philosophical stream creates a phrase it happens so that provides the perception of thought as established, based on life experience. The paradox of what was said, which is based on an oxymoron, is striking. In the manner characteristic of modern prose – not to highlight the traditional punctuation of direct speech – there are some sentences that belong to the characters. Syntactic parallelism is based on contextual antonyms. The key in the life conclusion of the main character of Odysseus is the lexical item love, repeated in different functions – as an object and a subject. Among the methods of stylistic syntax, the design of philosophical maxims for the language of V. Yermolenko’s novel is characterized by anaphora, often combined with syntactic parallelism, which ensure contexts with features of aphorism, provided by sentence structure and construction of complex syntactic wholes. To the above techniques, the author adds a gradation created by metaphorical images. The transition to the final chord of thought is made through hyperbole with rhetorical negation. Aphorism enriches the language of the novel, causes deeper reflection on what is stated. Many CSW are devoted to the understanding of love. The development of the micro-theme of one of the CSW is the definition of the concept of «love» and the transmission of what people embody into this feeling. Two views on the feeling of love are contrasted: the narrator’s and the usual, given by the predicate considered. We observe a combination of anaphoric and epiphoric repetitions in the context of reflections on love. Thus, the writer places logically accented words in a strong position. There are CSW in the novel, in which the psychological and philosophical basis of different behaviour of a man and a woman in love is subtly revealed. Different types of repetition, combined in contexts, allow you to concentrate thought. Parcelling, in particular of the main sentence parts, constantly contributes to the expression of the statement. Artistic definitions of happiness, embedded in the speech of the protagonist, begin with an anaphoric repetition of the key lexical item of CSW and are concretized by subordinate parts. The image of happiness is identified in the metaphor with various concepts – memory, thread, conspiracy, and mystery, which unite two people. As an analysis shows, in the philosophical reflections of the novel the repetitions of supporting lexical items, as well as the amplification of subordinate parts of one semantics are actively used. Thus, in the CSW with the micro-theme «war» the pronoun each is repeated in the subject function and the subordinate sentences of a goal are amplified. Originality. The narrative of V. Yermolenko’s novel «Ocean Catcher. The History of Odysseus» is characterized by philosophical reflections and maxims, which are embodied mainly in compound sentences, mostly complex ones, the subjunctive parts of which have different semantics (explanatory, substantive-defining, of a goal, of a reason). The writer actively uses repetitions of key images or supporting lexical items with a generalizing meaning, which contributes to the aphoristic presentation. Created anaphors serve to concentrate thought, whereas syntactic parallelism structures it for expression and clarity of perception. Conclusion. The rich verbal imagery of the novel and the manner of the narrative presuppose further multifaceted linguistic research.